Investigating Learner’s Experiences with AI-Enhanced Interactive Materials in Developing English Language Proficiency - Engelina Salainti; La Sunra (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study investigates two aspects: the English language learners' experiences and perceptions when using AI-enhanced interactive materials to develop their English language proficiency. Learning experience using AI in today's modern era is a common thing and is commonly used by students, especially English learners. The rapid development of technology has created several tools that help several fields, especially in English Education. AI-powered tools are created, and digital technologies continue to transform language learning environments. It is crucial to understand how emerging AI-powered tools impact the learner experience. The study explores the affordances and challenges of AI-enhanced interactive materials from the perspectives of language learners. Using a mixed-methods approach, by doing interviews and giving questionnaires the research collects and analyzes data on learners' engagement, motivation, skill development, and overall satisfaction with AI-powered learning resources. The results provide important preliminary information about the use of AI to improve interactive language learning materials in English learner classrooms and suggest directions for using these technologies effectively to build students' ability with oral academic English. This article is part of the thematic collection: Pedagogical Applications of AI In SLA (Second Language Acquisition).